(untitled) (Medical Forum Monthly, 2024)
Objectives:1.To determine changes of serum albumin level during progression of pregnancy. 2. To assess hypoalbuminaemia as an early indicator of pregnancy induced hypertension. Study Design: Comparative cross sectional study. Place and Duration of Study: The study was conducted at Biochemistry department of Liaquat University of Medical and Health Sciences, Jamshoro with the collaboration of Gynecological and obstetric department of Liaquat University Hospital, Jamshoro/Hyderabad from 1.8.2008 to 31.7.2009. Materials and Methods: One hundred & twenty pregnant women of different gestational stages were selected through convenient sampling. The women suffering from any systemic disease were excluded from the study. The data regarding subjects was collected on a prtested questionnaire.The blood samples were collected through sterilized disposable syringes from the anterior cubital vein by venipuncture & were transferred into test tube and allowed to clot and then centrifugeted & the readings were noted for each blood sample.Results were analyzed by SPSS version 14. Continuous predictor variable and its relationship to the outcome variable was examined to ensure its modeling as a linear term. where possible. The independent effect of each variable significantly associated with serum albumin level was assessed at significance level of P .05. Students t -test was applied to compare levels of serum albumin in case and control subjects. Results: The women of 25 years had highest percentage of 22%;the highest percent of 12% were in their 28th weeks of pregnancy. At the significant level of P= 0.05 Pearson’s coefficient was -0.267 and p-value was 0.003. As the duration of pregnancy advanced, level of serum albumin decreased in our study subjects. Conclusion: Appropriate measures should be taken to prevent fluctuation in serum albumin level which ultimately cause high maternal and neonatal mortality